Gestão sustentável: um estudo de caso da PUC-SP Campus Barueri - Belloque, Maria Carolina Mirabella (2011)
This research examined the concepts of sustainability on an university campus. To sustain this theme, firstly it was brought up the debate on need to seek a sustainable development, then the challenge that organizations face to suit this purpose and, finally, the reflection on the role of the university on this perspective. Thus, the questions that establish the course of the study are: what is a sustainable campus? And how does it work a management model that integrates the values of sustainability? To answer the first question, it was looked for support in the academic theoretical framework. The aspects that indicate the sustainability of a university campus were analyzed and a chart that synthetizes these aspects was made, being applied as a standard for the field study. The field study aimed to answer the second question of this research: how does it work a management model that integrates the values of sustainability? This was accomplished through a case study on the campus of PUC-SP at Barueri. Data collection for this study came about through in-depth interviews conducted with employees from the campus, analysis of documents provided by the direction of campus and participant observation conducted by the researcher. Evidence shows that the social group under analysis is in an early stage of the quest for sustainability. However, it presents actions on almost all the investigated aspects. The analysis of the campus was made through positive and negative considerations about each of the aspects investigated, of which the negative reviews were brought by the interviewees themselves. Although sustainability is in the agenda of most organizations and under an intense debate, many questions remain to be investigated about the role of the university on the sustainable development and about the real contributions it can offer to this subject. Through the debate established in this research and its field study, it was possible to analyze the interaction of the theoretical dimension and what actually occurs in a real context